Régimen de incorporación fiscal - Margin Manautou, Emilio (UNIVERSIDAD DE SONORA, 2016)
The document explains the Tax Incorporation Regime (RIF) which according to the SAT aims to bring together in a single body to taxpayers with related characteristics with the objective that after a certain period will be incorporated into the general scheme of the Income Tax Act, and concluded that "who designed the RIF, extinguished the (REPECOS) "human" problem, but affecting to the really small taxpayer that at the end......it will mean ... higher expenditure more than economic benefit to the SAT.